(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the comparative analysis of opposition movement in Ukraine and Poland in 70-80- es of the XX century. The author examines the basic flows of opposition movement: labor, religious, human rights, cultural. It is marked that in Ukraine opposition movement had brightly expressed national liberation direction, oriented to achievement of sovereignty and creation of the independent state, unlike Poland where opposition movement was anticommunist, oriented to deprivation from the soviet influence.